2020
DOI: 10.1002/psp4.12562
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically‐Based Pharmacokinetic Modeling for the Prediction of a Drug–Drug Interaction of Combined Effects on P‐glycoprotein and Cytochrome P450 3A

Abstract: Direct oral anticoagulants, like apixaban and rivaroxaban, are important for the treatment and prophylaxis of venous thromboembolism and to reduce the risk of stroke and systemic embolism in patients with nonvalvular atrial fibrillation. Since apixaban and rivaroxaban are predominantly eliminated by CYP3A and P-glycoprotein (P-gp), concomitant use of combined P-gp and strong CYP3A4 inhibitors and inducers should be avoided. Physiologically-based pharmacokinetic (PBPK) models for apixaban and rivaroxaban were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…20 Subsequently, the vendor-verified verapamil and norverapamil models from Simcyp (Certara UK Ltd., Simcyp Division, Sheffield, UK) have been applied to the DDI prediction with bosutinib, dabigatran etexilate, and rivaroxaban with or without modifications. [27][28][29][30] Pgp K i values used in these models were 0.10 to 0.16 μM for verapamil and 0.04 to 0.3 μM for norverapamil, whereas PBPK models often utilized the lower end of the reported in vitro K i values as the worst-case scenario. Overall, in these reports, only one Pgp substrate was used for the model verification and/or application, resulting in no comparisons of the predictive model performance among the different Pgp substrates.…”
Section: How Might This Change Drug Discovery Development And/ortherapeutics?mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Subsequently, the vendor-verified verapamil and norverapamil models from Simcyp (Certara UK Ltd., Simcyp Division, Sheffield, UK) have been applied to the DDI prediction with bosutinib, dabigatran etexilate, and rivaroxaban with or without modifications. [27][28][29][30] Pgp K i values used in these models were 0.10 to 0.16 μM for verapamil and 0.04 to 0.3 μM for norverapamil, whereas PBPK models often utilized the lower end of the reported in vitro K i values as the worst-case scenario. Overall, in these reports, only one Pgp substrate was used for the model verification and/or application, resulting in no comparisons of the predictive model performance among the different Pgp substrates.…”
Section: How Might This Change Drug Discovery Development And/ortherapeutics?mentioning
confidence: 99%
“…PBPK models for verapamil and norverapamil were reported to account for the effects of both Pgp and CYP3A inhibition on DDIs with digoxin and midazolam, respectively 20 . Subsequently, the vendor‐verified verapamil and norverapamil models from Simcyp (Certara UK Ltd., Simcyp Division, Sheffield, UK) have been applied to the DDI prediction with bosutinib, dabigatran etexilate, and rivaroxaban with or without modifications 27–30 . Pgp K i values used in these models were 0.10 to 0.16 μM for verapamil and 0.04 to 0.3 μM for norverapamil, whereas PBPK models often utilized the lower end of the reported in vitro K i values as the worst‐case scenario.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Grillo et al estimated the fractional CYP3A4 and CYP2J2 metabolism in the liver to be 0.37 and 0.29 respectively in their PBPK analysis, and utilizing similar estimates, we previously demonstrated how the enzyme-mediated DDI between rivaroxaban and ketoconazole (CYP3A4/2J2 inhibitor) was adequately recapitulated. 7,8 Conversely, Otsuka et al adjusted the fractional CYP3A4/2J2 metabolism to recapitulate the extent of DDI between rivaroxaban and fluconazole, 59 and neither OAT3 interaction nor simulation of the reduced CL R of rivaroxaban due to the clinical DDI with fluconazole was considered. 44 As our preliminary data demonstrated that fluconazole is an inhibitor of OAT3-mediated uptake of rivaroxaban (Figure S4), future PBPK modelling of this DDI should be performed with the consideration of OAT3 interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The apixaban and rivaroxaban PBPK models were based on the study by Otsuka et al and were kindly provided by the authors [20]. In the study by Otsuka et al, the rivaroxaban model was validated with the DDI study results with ketoconazole, ritonavir, clarithromycin, erythromycin, verapamil, and rifampicin.…”
Section: Application Of the Pbpk Model To Predict The Drug-drug Inter...mentioning
confidence: 99%